2011
DOI: 10.3390/s110201819
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Piezoresistive MEMS Strain Sensor with Low Thermal Sensitivity

Abstract: This paper presents the experimental evaluation of a new piezoresistive MEMS strain sensor. Geometric characteristics of the sensor silicon carrier have been employed to improve the sensor sensitivity. Surface features or trenches have been introduced in the vicinity of the sensing elements. These features create stress concentration regions (SCRs) and as a result, the strain/stress field was altered. The improved sensing sensitivity compensated for the signal loss. The feasibility of this methodology was prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 35 publications
0
26
1
Order By: Relevance
“…They have been widely used as stress and strain sensors. In the works of [2]- [9] have demonstrated that it is possible to model, the thermal behavior of the piezoresistive pressure sensor by adopting one approach based on the thermal behavior of piezoresistance. In this work, we modeled the thermal behavior of the piezoresistive pressure sensor by adopting a simple approach based on the thermal drift of the piezoresistive coefficients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been widely used as stress and strain sensors. In the works of [2]- [9] have demonstrated that it is possible to model, the thermal behavior of the piezoresistive pressure sensor by adopting one approach based on the thermal behavior of piezoresistance. In this work, we modeled the thermal behavior of the piezoresistive pressure sensor by adopting a simple approach based on the thermal drift of the piezoresistive coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, we adopted the model of Kanda [7]. A comparative study of the model with experimental results [8] [9] demonstrated that Kanda's model gives good estimate of the piezoresistance coefficient. After this, we will then devote a study of the effect of temperature and doping concentration on the piezoresistivity.…”
Section: Introductionmentioning
confidence: 99%
“…Finite Element Analysis (FEA) has been widely used in sensor analysis and design [2224] as an alternative to the analytical models. So far, only a few studies have been found [18,25–29] with respect to QTFs.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the same thermal expansion in the x-direction (biaxial stress: σ 11 = σ 22 ) and identical longitudinal and transversal piezoresistive coefficients for p-type silicon along the [110] directions, the thermal stress offset is compensated and would not result in a response at the bridge [6] (see eq. 2: Ф = 0/π 44 >> π 11 , π 12 /α 1 T+α 2 T 2 +…= account for the TCRs of the piezoresistive element).…”
Section: Thermal Simulationmentioning
confidence: 99%